Functions of CD1d-Restricted Invariant Natural Killer T Cells in Antimicrobial Immunity and Potential Applications for Infection Control - Kinjo, Yuki; Takatsuka, Shogo; Kitano, Naoki; Kawakubo, Shun; Abe, Masahiro; Ueno, Keigo; Miyazaki, Yoshitsugu (Frontiers in Immunology, 2018)
CD1d-restricted invariant natural killer T (iNKT) cells are innate-type lymphocytes that express a T-cell receptor (TCR) containing an invariant alpha chain encoded by the V alpha 14 gene in mice and V alpha 24 gene in humans. These iNKT cells recognize endogenous, microbial, and synthetic glycolipid antigens presented by the major histocompatibility complex (MHC) class I-like molecule CD1d. Upon TCR stimulation by glycolipid antigens, iNKT cells rapidly produce large amounts of cytokines, including interferon-gamma (IFNgamma) and interleukin-4 (IL-4). Activated iNKT cells contribute to host protection against a broad spectrum of microbial pathogens, and glycolipid-mediated stimulation of iNKT cells ameliorates many microbial infections by augmenting innate and acquired immunity. In some cases, however, antigen-activated iNKT cells exacerbate microbial infections by promoting pathogenic inflammation. Therefore, it is important to identify appropriate microbial targets for the application of iNKT cell activation as a treatment or vaccine adjuvant. Many studies have found that iNKT cell activation induces potent adjuvant activities promoting protective vaccine effects. In this review, we summarize the functions of CD1d-restricted iNKT cells in immune responses against microbial pathogens and describe the potential applications of glycolipid-mediated iNKT cell activation for preventing and controlling microbial infections.